ICD replacement in patients with intermediate left ventricular dysfunction under optimal medical treatment. (15th October 2019) - Artico, Jessica; Ceolin, Roberto; Franco, Stefania; Paldino, Alessia; Biondi, Federico; Barbati, Giulia; Gentile, Piero; Cannatà, Antonio; Zecchin, Massimo; Carriere, Cosimo; Merlo, Marco; Sinagra, Gianfranco
Abstract: Background: Implantable cardioverter-defibrillators (ICD) have a pivotal role in preventing major arrhythmic events in patients with severely reduced left ventricular ejection fraction (LVEF). Device replacement strategy is still controversial in patients without severely reduced left ventricular ejection fraction (LVEF) at the end of battery life. Objective: To evaluate the long-term arrhythmic outcome of patients with ICD or and cardiac resynchronization therapy defibrillators (CRT-D) with normal or intermediate LVEF at the time of device replacement. Methods: All consecutive patients with reduced ejection fraction heart failure, both from ischemic and non-ischemic origin, implanted with ICD or CRT-D for primary prevention from 2002 to 2009, were considered. The study population included patients without previous ICD interventions and without severe dysfunction (i.e. LVEF ≥ 35%) 60 [53–65] months after implantation (average battery duration). The outcome measure was the occurrence of appropriate ICD interventions in the long-term. Results: Among the 255 patients (150 ICDs; 105 CRT-D) evaluated, 45 (18%) had LVEF ≥ 35% without ICD interventions 5-year follow-up after implantation (15 ICD [10%]; 30 CRT-D [29%]). In the long term, ICD interventions were 4 (27%) in the ICD group and 5 (17%) in the CRT-D group. Conclusions: Despite the absence of severe left ventricular dysfunction at the time of battery replacement, a not negligible number of patients with ICD and CRT-D maintained a high risk of appropriate interventions in the long term, suggesting the opportunity of replacing the ICD regardless the amount of LV dysfunction. Highlights: Risk-benefit balance of ICD replacement is still controversial. Identifying patients at risk for arrhythmic events during follow-up is essential. Improved patients appears still at risk of ventricular arrhythmias during follow-up Device replacement is still recommended at the time of battery replacement.